(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Efficient pharmacy planning is essential for ensuring the availability of medications, optimizing resource utilization, and enhancing patient care in healthcare facilities. This comprehensive research investigates various aspects of pharmacy planning, including inventory management, procurement strategies, technology integration, and staff training initiatives. By synthesizing insights from academic literature, industry reports, and real-world case studies, this paper offers actionable recommendations to advance pharmacy planning practices and improve overall healthcare delivery.